2015
DOI: 10.1519/jsc.0000000000000749
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Rotational Mobility and Power on Throwing Velocity

Abstract: Talukdar, K, Cronin, J, Zois, J, and Sharp, AP. The role of rotational mobility and power on throwing velocity. J Strength Cond Res 29(4): 905-911, 2015-Sound rotational power and mobility are an integral component in functional performances, such as throwing and striking. The purpose of this study was to examine the role of rotational power and mobility on cricket ball-throwing velocity. Eleven professional cricketers and 10 under-19 club-level cricketers performed the chop and lift, seated and standing crick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 17 publications
3
19
0
Order By: Relevance
“…The cricketers in this study threw with greater velocity than elite junior male and subelite senior male cricketers previously investigated (14); however, they threw with lower velocities than elite senior male cricket players (14,30) and also collegiate (21) and professional (9) level male baseball players. Although the ball used in cricket is slightly larger (7.2 vs. 6.7 cm diameter) and heavier (156 vs. 142 g) than in baseball, cricket players repeatedly demonstrate inferior throwing velocities compared with baseball players, even when throwing the same size and weight (cricket) ball (16).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The cricketers in this study threw with greater velocity than elite junior male and subelite senior male cricketers previously investigated (14); however, they threw with lower velocities than elite senior male cricket players (14,30) and also collegiate (21) and professional (9) level male baseball players. Although the ball used in cricket is slightly larger (7.2 vs. 6.7 cm diameter) and heavier (156 vs. 142 g) than in baseball, cricket players repeatedly demonstrate inferior throwing velocities compared with baseball players, even when throwing the same size and weight (cricket) ball (16).…”
Section: Discussionmentioning
confidence: 53%
“…Despite the importance of throwing velocity to successful outcomes in the sport of cricket, however, only 1 study to date has explored the relationship between strength and/or power and throwing velocity in a group of cricket players (30). Although this study found significant force production differences between faster and slower throwing cricketers during a chop rotation movement, it used relatively few strength and/or power measures.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Conversely, Kohmura et al (2008) reported that the scoop medicine ball throw has very little shared variance with baseball fielding (throwing distance, standing long jump, and agility T-test) (~7%) compared with batting (~14%). Recently, Talukdar, Cronin, Zois, and Sharp (2015) examined the role of rotational power and mobility on cricet ball throwing velocity using a linear position transducer attached to the weight stack of a cable pulley system to measure chop and lift power. According to the authors, greater ROM at proximal segments, such as hips and thoracic, may not increase throwing velocity in cricet as reduced ROM at proximal segments can be useful in transfering the momentum from the lower extremity in an explosive task such as throwing.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore is no surprise that corestrengthening exercises have also become a part of amateur and professional sportsmen training (Hibbs et al 2008; Kibler et al 2006). Core exercises are also used as an important part in long term conditioning, to gain maximal performance in most sports (Lehman 2006 important to assess athletic ability that replicates as closely as possible the rotational activity of an athlete (Talukdar et al 2015). Effective execution of movement requires also strength and power of trunk muscles.These muscles (erector spinae, abdominal oblique, and rectus abdominis) are particularly active during the acceleration phase of trunk rotations (Bae 2012).…”
Section: Introductionmentioning
confidence: 99%